Acoustic analysis of a three-dimensional cylindrical shell model under electromagnetic vibration - Xu, Yanming; Wang, Jiachen; Yang, Sen; Lei, Guang; Zhao, Kuanyao (Frontiers in Physics, 2024)
This paper presents the acoustic analysis of a three-dimensional cylindrical shell model under electromagnetic vibration, a critical factor affecting the performance of electric motors in various applications such as automotive, aerospace, and industrial systems. The study provides the use of a multidisciplinary approach that integrates electromagnetics, structural vibration and acoustics, solved using the fast multipole boundary element method (FMBEM). The results summarize the validation of the analytical models and numerical simulations, offering insights into effective vibration reduction methods. The conclusions indicate that the 3-D numerical analysis using FMBEM aligns well with the analytical solution for the sound pressure in the exterior acoustic domain of the cylindrical shell model. The paper contributes valuable insights for the design of low-noise motors and the control of electromagnetic vibration and noise in electric motors.